PELAKSANAAN PEKERJAAN LAPIS PONDASI BAWAH UNTUK MEMPERTAHANKAN UMUR RENCANA JALAN - Adiwijaya Adiwijaya (LPPM Politeknik LP3I Medan, 2019)
This study contains the implementation of the bottom layer work in order to maintain the life of road plan. The preparation of lower layer pavement was followed method by SNI (Indonesian National Standard), the requirements of the material used are followed ASTM method. Based on the results, it was found that the mismatch of the road plan life were due to five factors, such as human resources error, the materials used and processing, the using of equipments, lack of quality control, and environmental factors that often cause damage to roads. High water content, frequent changes of weather, increade traffic loads and subgrade conditions were also affects the life of road plan.